Therapeutic Effect and Location of GFP-Labeled Placental Mesenchymal Stem Cells on Hepatic Fibrosis in Rats - Jiong Yu; Guangshu Hao; Dan Wang; Jingqi Liu; Xiaotian Dong; Yanni Sun; Qiaoling Pan; Yang Li; Xiaowei Shi; Lanjuan Li; Hongcui Cao (Stem Cells International)
Background. Liver fibrosis is a chronic progressive liver disease, but no established effective treatment exists except for liver transplantation. The present study was designed to investigate the effect of human placenta mesenchymal stem cells (hPMSCs) expressing green fluorescent protein (GFP) on carbon tetrachloride- (CCl4-) induced liver fibrosis in rats. Methods. Liver fibrosis was induced by subcutaneous injection with CCl4; hPMSCs were directly transplanted into rats through the caudal vein. The therapeutic efficacy of hPMSCs on liver fibrosis was measured by liver function tests, liver elastography, histopathology, Masson’s trichrome and Sirius red staining, and immunohistochemical studies. The expression levels of fibrotic markers, transforming growth factor β1 (TGF-β1) and α-smooth muscle actin (α-SMA), were assessed using real-time polymerase chain reaction. Results. We demonstrated that liver fibrosis was significantly dampened in the hPMSC transplantation group according to the Laennec fibrosis scoring system and histological data. The Sirius red-stained collagen area and the elastography score were significantly reduced in the hPMSC-treated group. Meanwhile, hPMSC administration significantly decreased TGF-β1 and α-SMA expression and enhanced liver functions in CCl4-induced fibrotic rats. Conclusion. This study indicates that transplantation of hPMSCs could repair liver fibrosis induced by CCl4 in rats, which may serve as a valuable therapeutic approach to treat liver diseases.